Analisis Bentuk Pelanggaran dan Upaya Penegakan Hak Orisinalitas Video Content Creator di Era Digital - Pandito Malim Hasayangan Tanjung; Diana Tantri Cahyaningsih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article is to review and analyze the forms of violation of originality rights in the context of video works and the efforts made by content creators if their originality rights are violated. this research identifies forms of Copyright infringement, especially related to reuploads without attribution or watermarks, as well as actions that can be taken by content creators in response to such violations, The research method used is a normative legal approach with a focus on analyzing primary and secondary legal materials through literature study. The results show that violations of originality rights often occur in various forms, such as unauthorized use, reproduction without significant changes, and unauthorized modification of original works. However, the main challenges in enforcing originality rights are the difficulty in identifying infringements in a timely manner and the cost and time involved in the enforcement process. cooperation between digital platforms, policymakers, and the creator community is needed to create a fairer and more supportive environment for creators to maintain the integrity of their original works and more effective efforts are needed to support video content creators to protect their originality rights in this digital era.